Renal involvement in autoinflammatory diseases - Changming Zhang; Jiahui Peng; Zhihong Liu; Qing Zhou (Karger Publishers, 2023)
Background: Autoinflammatory diseases (AIDs) were first proposed 20 years ago and caused by dysregulation of the innate immune system leading to episodes of systemic inflammation. Advances in next-generation sequencing and biological technology have resulted in the identification of new monogenic diseases and the corresponding signaling pathways that may guide us in targeted therapy. The kidney is a major target organ of various inflammatory process. Summary: During systemic inflammation, increased proinflammatory cytokines, such as IL-6, IL-1β and TNF, lead to over transcription and release of acute phase reactant serum amyloid A (SAA). Sustained high SAA levels promote a cascade of pathophysiological events, including protein misfolding, protein fragmentation and aggregation into highly ordered amyloid fibrils. Amyloid fibrils deposition in kidney cause progressive glomerular and vascular damage. Renal AA amyloidosis is a common and severe complication of AIDs, including FMF, CAPS, TRAPS, MKD/HIDS, and DADA2. Amyloidosis may even be the first clinical manifestation in some patients, presenting with asymtomatic proteinuria, nephritic syndrome, progressive renal insufficiency or end-stage kidney disease. In addition, major dysregulated pathways in different AIDs lead to endogenous inflammation, which is due to direct endothelial cytotoxicity caused by IL-1β, type I interferon, or possibly immune complexes. The kidney is frequently affected by various vasculitis and renal involvement is a major determinant of treatment options and outcomes. The renal vasculitis involved in AIDs includes renal artery Takayasu vasculitis, polyarteritis nodosa, and IgA vasculitis. Moreover, other kidney diseases, such as glomerulonephritis, lupus nephritis, and renal tubular dysfunction were also reported in AIDs. Key Messages: Kidney manifestations can be a coexisting disease seen with AIDs. They may also be one of the characteristics of AIDs. Clinicians should be aware of the possibility that amyloidosis, vasculitis or other renal diseases may be associated with AIDs in order to make appropriate diagnosis and treatment. Renal biopsy may be of great significance. Biologics, which switch off the underlying cytokine mediated inflammatory process, have the potential to restore organ damage and improve the outcome in the very early stage of the disease.